2020
DOI: 10.21203/rs.3.rs-21980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring social media attention of scientific research on Novel Coronavirus Disease 2019 (COVID-19): An investigation on article-level metrics data of Dimensions

Abstract: The purpose of this research was to evaluate the rate of attention to the scientific productions on COVID-19 in social media over a period of four months. The present research was an applied descriptive-analytical study that used Scientometrics analysis. The population study included research papers about the COVID-19 indexed in Dimensions platform from December 2019 to March 2020. Information of 20% of the articles with the highest citation count and 20% of the articles with the highest number of Altmetric At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Themes of previous studies that focus on exploration of, description of, correlation of, or predictive modeling with Twitter data during COVID-19 pandemic include sentiment analysis [17,[25][26][27][28], public attitude/interest measurement [21,[29][30][31], content analysis [15,[32][33][34][35][36], topic modeling [16,26,27,[37][38][39][40], analysis of misinformation, disinformation, or conspiracies [20,[41][42][43][44][45][46], outbreak detection or disease nowcasting/forecasting [18,19], and more [47][48][49][50][51][52]. Similarly, data from other social media channels (e.g., Weibo, Reddit, Facebook) or search engine statistics are utilized for parallel analyses related to COVID-19 pandemic as well [53][54][55][56][57][58][59][60][61]…”
Section: Going Beyond Correlationsmentioning
confidence: 99%
“…Themes of previous studies that focus on exploration of, description of, correlation of, or predictive modeling with Twitter data during COVID-19 pandemic include sentiment analysis [17,[25][26][27][28], public attitude/interest measurement [21,[29][30][31], content analysis [15,[32][33][34][35][36], topic modeling [16,26,27,[37][38][39][40], analysis of misinformation, disinformation, or conspiracies [20,[41][42][43][44][45][46], outbreak detection or disease nowcasting/forecasting [18,19], and more [47][48][49][50][51][52]. Similarly, data from other social media channels (e.g., Weibo, Reddit, Facebook) or search engine statistics are utilized for parallel analyses related to COVID-19 pandemic as well [53][54][55][56][57][58][59][60][61]…”
Section: Going Beyond Correlationsmentioning
confidence: 99%
“…For example, Mahmoudi [9] found that most of the top papers' authors about the virus are males, while women represented a small percentage of the papers. Batooli and Sayyah [10] showed that one of the characteristics of the virus research is that a significant portion of the authors is from China and Japan. The study also revealed a correlation between Altmetrics and bibliometrics, which means that Altmetrics can serve as an indicator of papers performance and citation count.…”
Section: Literaturementioning
confidence: 99%
“…Themes of previous studies that focus on exploration of, description of, correlation of, or predictive modeling with Twitter data during COVID-19 pandemic include sentiment analysis [17], [25], [26], [27], [28], public attitude/interest measurement [21], [29], [30], [31], content analysis [32], [33], [15], [34], [35], [36], topic modeling [37], [16], [38], [39], [40], [26], [27], analysis of misinformation, disinformation, or conspiracies [41], [20], [42], [43], [44], [45], [46], outbreak detection or disease nowcasting/forecasting [19], [18], and more [47], [48], [49], [50], [51], [52]. Similarly, data from other social media channels (e.g.…”
Section: Going Beyond Correlationsmentioning
confidence: 99%